The acute effect of various feedback approaches on sprint performance, motivation, and affective mood states in highly trained female athletes: a randomized crossover trial - Di Bella, L.; Doma, K.; Sinclair, W. H.; Connor, J. D. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This crossover trial compared the effects of varying feedback approaches on sprint performance, motivation, and affective mood states in female athletes.